How well can an ensemble predict the uncertainty in the location of winter storm precipitation?. Issue 1 (1st January 2018) - Han, Fan; Szunyogh, Istvan
Abstract: A pair of morphing-based ensemble forecast diagnostics is proposed for the verification of the location of precipitation events. The diagnostics are applied to operational global ensemble forecasts of winter storms in the United States in the winters of 2014/2015 and 2015/2016. A slowly developing systematic error is found to lead to an unrealistically fast eastward propagation of the storms in the week-two forecasts. Apart from this systematic error, the forecasts predict the uncertainty in the location of the precipitation events reliably. They, however, also grossly underestimate the uncertainty of the amount of precipitation in the short (shorter than 5 days) forecast range.